Local-to-global signal transduction at the core of a Mn2+ sensing riboswitch - Krishna C. Suddala (Nature Portfolio, 2019)
Riboswitches bind intracellular metabolites and control bacterial gene expression. Here, by using X-ray crystallography, molecular dynamics simulations, and single-molecule fluorescence resonance energy transfer, the authors show how a local Mn2+ ion-binding signal is transduced across the yybP-ykoY riboswitch from Xanthomonas oryzae.